2021
DOI: 10.3390/geosciences11020069
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Studies Using Electrical Resistivity Tomography and Fiber Optic Techniques to Detect Seepage Zones in River Embankments

Abstract: We present the results of laboratory experiments on a down-scaled river levee constructed with clayey material collected from a river embankment where a permanent resistivity instrument has operated since 2015. To create potential seepages through the levee, two zones (5 × 4 cm and 10 × 2 cm) were filled with sand during the levee construction. Electrical resistivity tomography (ERT) technique and Fiber Bragg Grating (FBG) technology were used to study time-lapse variations due to seepage. The ERT profile was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Although the authors were able to successfully monitor the leakage from the tank, it is stated that results are significantly influenced with metal presence. Within a more recent study, Hojat et al (2021) demonstrated the seepage from a river levee in a laboratory experiment implemented with ERT during two stages of leakage (Figure 4) and concluded that ERT is capable to detect the seepage in early stages.…”
Section: Electrical Resistivity Tomography (Ert)mentioning
confidence: 94%
“…Although the authors were able to successfully monitor the leakage from the tank, it is stated that results are significantly influenced with metal presence. Within a more recent study, Hojat et al (2021) demonstrated the seepage from a river levee in a laboratory experiment implemented with ERT during two stages of leakage (Figure 4) and concluded that ERT is capable to detect the seepage in early stages.…”
Section: Electrical Resistivity Tomography (Ert)mentioning
confidence: 94%
“…A possible regularisation method is an elastic net, defined as a linear mixture of a Selection Operator (LASSO), Least Absolute Shrinkage and ridge regression, which is called Tikhonov regularisation [52,53]. Instead of the solution of classical task (5), which is connected with an estimation of unknown parameters in the logistic regression model, we optimise the objective function (6) whilst taking the penalty into account. In order to do this, we need to solve the following equation:…”
Section: Elastic Netmentioning
confidence: 99%
“…This solution determines changes in the physical parameters of the tested object (resistivity). Finally, electrical resistivity tomography (ERT) [4][5][6] is used to study shafts. The resistivity tomography method consists of placing the measuring electrodes along the profile line at equal distances.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are widely utilized due to their rapid speed and cost effectiveness [9]. They have been extensively applied in the leakage investigations and analyses of various engineering structures, such as dams, levees, and tailings dams [10][11][12][13][14]. Additionally, they have been applied in geological environmental analyses of features, such as karst, culverts, and other geological structures [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%